2022
DOI: 10.1093/nar/gkac880
|View full text |Cite
|
Sign up to set email alerts
|

Molecular basis of dual anti-CRISPR and auto-regulatory functions of AcrIF24

Abstract: CRISPR-Cas systems are adaptive immune systems in bacteria and archaea that provide resistance against phages and other mobile genetic elements. To fight against CRISPR-Cas systems, phages and archaeal viruses encode anti-CRISPR (Acr) proteins that inhibit CRISPR-Cas systems. The expression of acr genes is controlled by anti-CRISPR-associated (Aca) proteins encoded within acr-aca operons. AcrIF24 is a recently identified Acr that inhibits the type I-F CRISPR-Cas system. Interestingly, AcrIF24 was predicted to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 60 publications
(78 reference statements)
0
3
0
Order By: Relevance
“…Indeed, while numerous Acrs are known to inhibit the activity of Cas9 as monomers, it has been demonstrated previously that certain Acrs exert their function in a dimeric configuration ( 12 , 45 ). In the case of AcrIIA28, the SEC result showed that AcrIIA28 was eluted between the molecular sizes of 17 and 1.35 kDa by producing one prominent peak in the chromatogram (Figure 1A ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, while numerous Acrs are known to inhibit the activity of Cas9 as monomers, it has been demonstrated previously that certain Acrs exert their function in a dimeric configuration ( 12 , 45 ). In the case of AcrIIA28, the SEC result showed that AcrIIA28 was eluted between the molecular sizes of 17 and 1.35 kDa by producing one prominent peak in the chromatogram (Figure 1A ).…”
Section: Resultsmentioning
confidence: 99%
“…Upon recognizing a complementary invader DNA sequence, the complex formed by the crRNA and Cas proteins catalyzes the cleavage of the invader's genetic material autonomously or by enlisting supplementary Cas proteins ( 7–10 ). Given the precision with which this bacterial immune system can incise specific DNA sites, CRISPR–Cas systems have found application in gene editing, enabling targeted modifications of genes for both experimental and medicinal objectives ( 11 , 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…In genomes of P. aeruginosa phages, regulatory mini-arrays were found within a known anti-CRISPR locus that encodes AcrIF23 and AcrIF24 (68). AcrIF24 binds the Cascade complex, preventing the recruitment of Cas3 (77-79), whereas AcrIF23 inhibits the nuclease activity of Cas3 (80). Combining these Acrs with distinct CRISPR inhibition mechanisms with a regulatory guide that down-regulates Cascade expression is consistent with a multipronged anti-CRISPR strategy that involves both inhibition of the activity of Cas proteins and prevention of further cas gene expression as recently demonstrated for phages evading type V systems (81).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the typical arrangement where acr and aca genes are separate within the same operon, certain Acrs are fusion proteins that combine both canonical Acr and Aca components: one domain responsible for inhibiting the CRISPR-Cas system, and the other domain containing an HTH motif. Several such bi-functional Acrs have been identified, including AcrIIA1 9 , 24 , 25 , AcrIIA6 16 , 26 , AcrIIA13-15 27 , and AcrIF24 28 30 .…”
Section: Introductionmentioning
confidence: 99%